Delayed Radial Nerve Palsy after Closed Reduction of a Pediatric Humeral Shaft Fracture - Runner, Robert (Case Rep Orthop, 2017)
Humeral shaft fractures are common in the United States and may be associated with radial nerve injuries due to their close anatomic relationship in the spiral groove. Most radial nerve palsies are found at presentation due to the initial trauma; however, they can present secondary to orthopaedic intervention following reduction. In this case report, we present a case of delayed radial nerve palsy in a pediatric patient that was identified four days after closed reduction and splinting which required open reduction, nerve exploration, and internal fixation. Fortunately, full motor and sensory recovery was observed at 6 weeks post-op. A unique aspect of this case is that immediate postreduction exam in the emergency department showed no signs of injury or entrapment of the radial nerve.